Topology, typology, and dynamics of commons-based peer production: On platforms, actors, and innovation in the maker movement - Venkat Aryan; Juergen Bertling; Christa Liedtke (Creativity and Innovation Management, 2021)
In this paper, we aim to present a comprehensive analysis on the emerging phenomenon of distributed innovation in commons-based peer production (CBPP) platforms. Starting with the exploration of the widely held belief on value-creation confined to industrial settings, we raise several questions regarding the feasibility of, and a need for, an inclusive innovation process that can tap grassroots capacity into both traditional (industrial research and development) and emerging (peer-to-peer) innovation models to yield sustainable solutions. In particular, we explore the emergence and structuration of digital innovations in the maker movement, as it presents an alternative construct of innovation wherein access to and sharing of knowledge is predominantly distributed. With innovation outcomes often freely revealed, its very structuration could pose a principal challenge to our conceptualizations of value creation and competitive advantage in the current economic model. Drawing from responses received from 200 collaborative innovation platforms, six semi-structured interviews focusing on socio-technical innovation cases, as well as four in-depth narrative interviews with maker turned entrepreneurs, we present a detailed analysis on the topology of network, typology of actors, as well as the underlying innovation ecosystem in CBPP networks in Germany. In doing so, we contribute to the conceptualization of peer-to-peer distributed innovations in collaborative platforms.
Keywords: 330; collaborative platforms; commons-based peer production (CBPP); digital innovation; digital manufacturing; distributed innovation; maker movement; open innovation platforms